Effects of NS2B-NS3 protease and furin inhibition on West Nile and Dengue virus replication - Kouretova, Jenny; Kallis, Stephanie; Bartenschlager, Ralf (Journal of enzyme inhibition and medicinal chemistry, 2017)
West Nile virus (WNV) and Dengue virus (DENV) replication depends on the viral NS2B-NS3 protease and the host enzyme furin, which emerged as potential drug targets. Modification of our previously described WNV protease inhibitors by basic phenylalanine analogs provided compounds with reduced potency against the WNV and DENV protease. In a second series, their decarboxylated P1-trans-(4-guanidino)cyclohexylamide was replaced by an arginyl-amide moiety. Compound 4-(guanidinomethyl)-phenylacetyl-Lys-Lys-Arg-NH2 inhibits the NS2B-NS3 protease of WNV with an inhibition constant of 0.11 µM. Due to the similarity in substrate specificity, we have also tested the potency of our previously described multibasic furin inhibitors. Their further modification provided chimeric inhibitors with additional potency against the WNV and DENV proteases. A strong inhibition of WNV and DENV replication in cell culture was observed for the specific furin inhibitors, which reduced virus titers up to 10,000-fold. These studies reveal that potent inhibitors of furin can block the replication of DENV and WNV.
Gesehen am 18.10.2018